2020
DOI: 10.1111/ggi.13907
|View full text |Cite
|
Sign up to set email alerts
|

Exercise cessation in active older adults: Effects on inflammatory markers and adiponectin

Abstract: Aim: To evaluate the effects of 3 months of exercise cessation in physically active older individuals on inflammatory biomarkers and adiponectin, and examine any association modifications in physical functioning. Methods:We evaluated the effects of exercise cessation in 49 physically active older adults on inflammatory biomarkers, adiponectin and physical functioning. Participants (38 women, 11 men) were aged >65 years old and had attended a 9-month supervised exercise program. After 3 months of exercise cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…With 12 weeks of aerobic exercise Prusik et al [10] reported a 7.7% improvement in upper body strength, 4.8% in lower body strength, 10.2% in agility and 28.5% in lower body flexibility. The cessation of exercise resulted in declines in FC and lipidic profile, although were not enough to reverse to baseline values [2,6,[38][39][40]. Padilha et al [41] with 12 weeks of detaining after 12 weeks of RT observed declines in FC but not significantly compared to baseline value.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…With 12 weeks of aerobic exercise Prusik et al [10] reported a 7.7% improvement in upper body strength, 4.8% in lower body strength, 10.2% in agility and 28.5% in lower body flexibility. The cessation of exercise resulted in declines in FC and lipidic profile, although were not enough to reverse to baseline values [2,6,[38][39][40]. Padilha et al [41] with 12 weeks of detaining after 12 weeks of RT observed declines in FC but not significantly compared to baseline value.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, physical inactivity is related to a higher prevalence of most CVD risk factors, including high values of blood glucose, total cholesterol (TC), triglycerides (TG), high blood pressure, metabolic syndrome and obesity [3,6]. Dyslipidemia (levels that are either higher or lower than normal range for blood fats such as TG and cholesterol, and uncontrolled serum blood levels of glucose have been shown to have enormous impact on CVD risk in women compared to men, due to menopause that accentuates the negative changes in body composition and metabolic profile [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TG, TC and GL maintained some of the benefits of METP, SBP and DPB returned to baseline values. With four weeks of detraining, Nolan et al [ 45 ] found no changes in TG, TC and blood pressure, and with a longer period, i.e., three months of DT after nine months of METP, Esain et al [ 46 ] reported no significant changes in TG and TC. One of the reasons for the results of these two studies may be the normal values at the baseline and after the exercise program of the participants compared to ours that had higher values of TG and TC at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agree with the substantial difference in the response between the experimental group and the control group in HbA1c levels obtained in the present study ( Figure 2). The lack of physical activity and a sedentary lifestyle lead to harmful responses related to insulin resistance and prediabetes indicators [62]. Tables 3 and 4 show that the two groups began with mild cognitive deterioration.…”
Section: Glycosylated Haemoglobinmentioning
confidence: 99%